Neuerwerbungen : 1977. - Städtisches Kunstmuseum Bonn (Bonn : Städtisches Kunstmuseum Bonn, 1978)
Byars, James Lee ; Canogar, Rafael ; Equipo Cronica ; Oppenheim, Dennis ; Vautier, Ben ; Palermo ; etc.
Neuerwerbungen : 1976, Städtisches Kunstmuseum Bonn, 7.6. - 27.8.1978
boek